Implementation of the polluter pays principle: comparative legal issues - Vadim A. Vinogradov; Larisa V. Soldatova (Правоприменение, 2020)
The subject. The article is devoted to the study of the polluter pays principle from the point of view of the mechanism for its implementation to ensure the right to a favorable environment.The purpose of the article is to identify the degree of implementation of polluter pays principle in Russian legislation in comparison with the OECD countries.    The methodology. The study is based on the comparative legal method, which allows us to analyze the strengths and weaknesses of the models of legal regulation of relations in the field of environmental protection chosen by different countries and international organizations. The study also relies on general scientific and private scientific methods, including formally legal method, interpretation of legal acts.The main results and scope of their application. The content of the polluter pays principle is determined, as well as the goal of its establishment and the methods used by legislator to achieve this goal. The effectiveness of the polluter pays principle is determined by an integrated regulatory approach. It includes several elements: not only the obligation to compensate for the harm caused in full, but also to take all necessary measures to prevent the possibility of harm at all stages of the activity, including design, construction, etc. The analysis of international legal regulation, as well as the regulatory legal acts of different countries shows that this principle is implemented in the legislation of many countries and an effective mechanism for its application is created in developed countries. Genuine implementation of this principle lets create balance between economic and environmental relations and protect the vital interests of human and society.Conclusions. A comparative analysis of the legal regulation of relations on environmental protection in terms of applying the polluter pays principle allows us to conclude that there is a rather formal approach to its implementation into Russian legislation. There is no comprehensive approach to the regulation of economic activity at all stages of its implementation, from planning and design to decommissioning and waste management. This, in turn, does not allow creating a balanced management mechanism of environmental protection in Russia. In this connection, a list of priority measures to create an effective legal regulation mechanism is proposed.